2011
DOI: 10.1152/ajpheart.01190.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and acute exposure of mouse hearts to fatty acids increases oxygen cost of excitation-contraction coupling

Abstract: Boardman NT, Larsen TS, Severson DL, Essop MF, Aasum E. Chronic and acute exposure of mouse hearts to fatty acids increases oxygen cost of excitation-contraction coupling. Am J Physiol Heart Circ Physiol 300: H1631-H1636, 2011. First published February 18, 2011 doi:10.1152/ajpheart.01190.2010The aim of the present study was to evaluate the underlying processes involved in the oxygen wasting induced by inotropic drugs and acute and chronic elevation of fatty acid (FA) supply, using unloaded perfused mouse hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
(97 reference statements)
3
11
1
Order By: Relevance
“…Our correlation data provide, however, some insight into linkages between cardiac metabolic flux and functional parameters, which need to be considered in data interpretation. Specifically, results from our correlation analyses concur and expand previously suggested associations between some specific fluxes and functional parameters, namely a positive association between glycolysis and functional parameters relevant to cardiac work (1,13,45) and the flux ratio relevant to exogenous FA oxidation (OLE/CS), MVO 2 , and myocardial perfusion (8,20,28,41). In addition, they are revealing some new ones, namely a positive correlation between flux ratios relevant to pyruvate oxidation (PDC/CS) or anaplerosis (PC/CS) and HR-related parameters.…”
Section: H83supporting
confidence: 89%
See 1 more Smart Citation
“…Our correlation data provide, however, some insight into linkages between cardiac metabolic flux and functional parameters, which need to be considered in data interpretation. Specifically, results from our correlation analyses concur and expand previously suggested associations between some specific fluxes and functional parameters, namely a positive association between glycolysis and functional parameters relevant to cardiac work (1,13,45) and the flux ratio relevant to exogenous FA oxidation (OLE/CS), MVO 2 , and myocardial perfusion (8,20,28,41). In addition, they are revealing some new ones, namely a positive correlation between flux ratios relevant to pyruvate oxidation (PDC/CS) or anaplerosis (PC/CS) and HR-related parameters.…”
Section: H83supporting
confidence: 89%
“…Considering that cardiac metabolism is closely related to function (24,33,35,40), we aimed at evaluating linkages between strain-dependent variations in metabolic flux and functional parameters. Previous studies have reported positive association 1) between glycolysis and functional parameters relevant to myocardial work (1,13,45) and 2) LCFA oxidation and myocardial perfusion (8,20,28,41). Because these associations were not readily apparent from mean values reported for the various cardiac functional ( Fig.…”
Section: H81mentioning
confidence: 90%
“…In addition, as the relaxation factor is elevated and thus relaxation is slowed, one may also speculate that the prolonged crossbridge cycling may consume ATP and O 2 without a gain in stroke volume (26). Finally, it should also be noted that mechanical inefficiency would be further exacerbated in vivo due to the potential O 2 wasting effect after ␤-adrenergic stimulation (10,29,41).…”
Section: Discussionmentioning
confidence: 99%
“…Work-independent MV O2 was measured in the retrograde perfused unloaded heart (MV O2 unloaded). By electrically arresting these hearts (elevation of extracellular K ϩ concentration), we could also measure the O2 cost of basal metabolism (MV O2 BM), and the difference between MV O2 unloaded and MV O2 BM was used to obtain the O2 cost of ECC (MV O2 ECC) (2,9,10,15).…”
Section: Animals Serca2mentioning
confidence: 99%
“…In addition, the increased UCP2 and UCP3 in heart, even if being associated with inefficiency of oxidative phosphorylation due to uncoupling, results in increased fatty acid oxidation as fuel utilization [92]. In several pathophysiological conditions such as insulin resistance, diabetes, and postischemia stressed heart, chronic exposure to elevated circulating FFAs leads to increased UCP3 as adaptations that afford protection against the detrimental effect of an acute FFA load [93, 94]. Indeed diabetic heart is characterized by UCP3 overexpression, increased fatty acid oxidation, increased myocardial oxygen consumption, and reduced cardiac efficiency [95].…”
Section: Ucps and Mitochondrial Fatty Acid Oxidationmentioning
confidence: 99%